Numerical analysis and its applications : 6th International Conference, NAA 2016, Lozenetz, Bulgaria, June 15-22, 2016, Revised selected papers /: 6th International Conference, NAA 2016, Lozenetz, Bulgaria, June 15-22, 2016, Revised selected papers. (2017) - Unknown
No abstract available